2019
DOI: 10.3390/w11081680
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Hydromorphological Variability in Greek Rivers: A Nationwide Assessment with Implications for Management

Abstract: European rivers are under ecological threat by a variety of stressors. Nutrient pollution, soil erosion, and alteration in hydrology are considered the most common problems that riverine ecosystems are facing today. Not surprisingly, river monitoring activities in Europe have been intensified during the last few years to fulfil the Water Framework Directive (WFD) requirements. With this article, we present a nationwide assessment of the water quality and hydromorphological variability in Greek Rivers based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The land-use types and the activities on the certain types (fertilization, irrigation, aquaculture, and heaviest) have the indirect influence on water quality [41,77,78]. The plantation is opposite to the others due to the large amount of fertilizer and less water (Figure 5a,b); as in the study area, the amounts of fertilizer in plantations are large [9].…”
Section: Water Body Configurations Land-use Patterns and Their Drivimentioning
confidence: 83%
See 1 more Smart Citation
“…The land-use types and the activities on the certain types (fertilization, irrigation, aquaculture, and heaviest) have the indirect influence on water quality [41,77,78]. The plantation is opposite to the others due to the large amount of fertilizer and less water (Figure 5a,b); as in the study area, the amounts of fertilizer in plantations are large [9].…”
Section: Water Body Configurations Land-use Patterns and Their Drivimentioning
confidence: 83%
“…The large subcatchments with big amounts of pollutant need to match the water bodies with high proportions and various types (Figures 1 and 4). Other researches also demonstrated that the upper regions with forest mainly usually can cut off 30% of nitrogen and phosphorus leaking than the lower regions with croplands and urban areas mainly [9,27,78]. Experiences in Lita Watershed can be applied in two situations, the areas where the water body types and shapes are adjustable and where the soil management is hard to realize.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Agricultural activity in particular is considered a major driver of hydromorphological modifications in Mediterranean rivers [15][16][17]. For instance, bank and channel resectioning is used as a practice of flood defense management to protect neighboring agricultural land from flood events.…”
Section: Discussionmentioning
confidence: 99%
“…In Greece, the monitoring of the biological quality elements (BQEs), the physicochemical and the hydromorphological conditions of all running waters in compliance with the WFD is implemented by the Institute of Marine Biological Resources and Inland Waters (IMBRIW) of the Hellenic Centre for Marine Research (HCMR). The sampling network extends to the whole national territory and is distributed among fourteen WFD River Basin Districts (RBDs) [15]. Hydromorphological features and modifications of the sites of the sampling network are recorded once for the duration of the monitoring period according to the River Habitat Survey (RHS) method.…”
Section: Introductionmentioning
confidence: 99%